Pengaruh Social Media Marketing dan Brand Ambassador Terhadap Minat Beli Pada Produk Scarlett Whitening - Sonia Silastia; Nadya Artha Joecha Mayvea; Salsabila Rahmadini; Rohanah Rohanah; Nabila Nabila; Elfiana Febrianti; Robiatul Adawiyah; Kurniawati Mulyanti (STIKes Ibnu Sina Ajibarang, 2024)
The study explores how consumer interest in purchasing Scarlett bleach products is influenced by the interaction between social media marketing and brand ambassadors. The purpose of this study was to investigate the potential impact of brand ambassadors and social media marketing on consumer interest in purchasing Scarlett Whitening products. Using purposive sampling, a non-probability sampling technique, 54 students who had purchased Scarlett products were respondents in total. Google Forms distributed questionnaires are used in the data collection method. The findings of the study showed that the t-value was 1.129 < 2.008 and that the social media marketing variable had a negative and insignificant impact on the variable that measured interest in buying Scarlett bleaching products, with an effect of 0.267 > 0.05. At 0.000 < 0.05 and 1 count 5.292 > t table 2.008, The Brand Ambassador variable has been proven to have a positive and rather significant effect on the variable of Scarlett Whitening's buying interest in products.